Review of Default Law in the Franchise Agreement Between the Franchisee and the Franschisor - Dharmawan, Jessica; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
Franchise is an option for entrepreneurship with the least risk. Initially, the franchise started from the success of the business of the brand owner or franchisor. Through the franchise business, the franchisor will transmit the success of his business to the franchisee. In a franchise or franchise business, the cooperation agreement between the two parties is called a franchise agreement. The franchise agreement is a legal guideline that outlines the responsibilities of the franchisor and franchisee. In the franchise agreement, the franchisor has several responsibilities regulated in Government Regulation no. 42 of 2007 concerning franchise business (Franchise). In this regulation, it has been explained what are the obligations of the franchisor before entering into a franchise agreement with the franchisee. This is so that the franchisee is not deceived which will cause losses to the franchisee.